2016
DOI: 10.1016/j.ejvs.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Aortic Aneurysm Genetic Associations: Mostly False? A Systematic Review and Meta-analysis

Abstract: Uncorrected multiple testing and flexible study design (particularly testing many inheritance models and subgroups, and failure to check for Hardy-Weinberg equilibrium) contributed to apparently false associations being reported. Heterogeneity, possibly due to the case mix, geographical, temporal, and environmental variation between different studies, was evident. Polymorphisms in nine genes had strong or moderate support on the basis of the literature at this time. Suggestions are made for improving AAA genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 114 publications
2
41
0
Order By: Relevance
“…It is no surprise that a significant part of the changed gene expression is related to genes involved in inflammatory processes, i.e. genes for chemokines, integrins, and those for T and B cell activation, similarly to the previously published studies (Biros et al 2014, Hinterseher et al 2013, Giusti et al 2009, Butt et al 2016, Tanios et al 2015. Destructive inflammation is the main characteristic of AAA formation and progression; it is therefore understandable that immunological mechanisms are at play.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It is no surprise that a significant part of the changed gene expression is related to genes involved in inflammatory processes, i.e. genes for chemokines, integrins, and those for T and B cell activation, similarly to the previously published studies (Biros et al 2014, Hinterseher et al 2013, Giusti et al 2009, Butt et al 2016, Tanios et al 2015. Destructive inflammation is the main characteristic of AAA formation and progression; it is therefore understandable that immunological mechanisms are at play.…”
Section: Discussionsupporting
confidence: 69%
“…Taking samples from the same patient represents a possible limitation of the study if the genetic factors played a significant role in the onset of the disease. While in the thoracic aortic aneurysms (TTA), we already know a specific list of genes that are undoubtedly associated with the pathogenesis of TAA, no mutation predicting the occurrence of AAA has yet been found (Carino et al 2018). Therefore, it will certainly not be a monogenic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Those differences were confirmed in many different cell types, such as macrophages, smooth muscle cells, and fibroblasts . The MMP3 gene polymorphism 1171dupA has been associated with many cardiovascular diseases such as: CHD, myocardial infarction, instable angina, ischemic stroke, deep venous thrombosis, abdominal aortic aneurysm, coronary artery stenosis, and hypertension . Numerous studies indicate the association between this polymorphism and coronary artery disease; however, the results are inconsistent.…”
Section: Introductionmentioning
confidence: 94%
“…Future screening studies may also evaluate genetic factors in association with presence of AAA, as it has been suggested that polymorphisms in some genes had strong or moderate association with AAA. 30 While the cost-effectiveness of the current screening programs is obvious, population stratification to identify the most vulnerable based on novel risk factors may further increase their efficacy and reduce costs, especially in consideration with the need for rescreening because of the aging population. Future screening programs may benefit from the inclusion of more targeted criteria in order to increase the number of detected AAAs.…”
mentioning
confidence: 99%